2020
DOI: 10.3389/fnins.2019.01345
|View full text |Cite
|
Sign up to set email alerts
|

Partial Reversal of Striatal Damage by Palmitoylethanolamide Administration Following Perinatal Asphyxia

Abstract: Perinatal asphyxia (PA) is a clinical condition brought by a birth temporary oxygen deprivation associated with long-term damage in the corpus striatum, one of the most compromised brain areas. Palmitoylethanolamide (PEA) is a neuromodulator well known for its protective effects in brain injury models, including PA, albeit not deeply studied regarding its particular effects in the corpus striatum following PA. Using Bjelke et al. (1991) PA model, full-term pregnant rats were decapitated, and uterus horns were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Recent evidence from our laboratory revealed that PA resulted in a short-term reduction in microtubule-associated protein 2 (MAP-2) immunostaining in the CA1 hippocampal area (Herrera et al, 2018) and the corpus striatum (Udovin et al, 2020), as was found at P30. Protein expression analysis by Western blot confirmed this dendritic alteration.…”
Section: Experimental Findings Supporting Pa-induced Synaptic Alteratmentioning
confidence: 63%
See 4 more Smart Citations
“…Recent evidence from our laboratory revealed that PA resulted in a short-term reduction in microtubule-associated protein 2 (MAP-2) immunostaining in the CA1 hippocampal area (Herrera et al, 2018) and the corpus striatum (Udovin et al, 2020), as was found at P30. Protein expression analysis by Western blot confirmed this dendritic alteration.…”
Section: Experimental Findings Supporting Pa-induced Synaptic Alteratmentioning
confidence: 63%
“…decrease in MAP-2 and pNF-H/M reactive areas, reversed the decrease in MAP-2 expression, and prevented pNF-H/M depletion Udovin et al (2020). …”
mentioning
confidence: 86%
See 3 more Smart Citations